قراءة في مسيرة منظمة الأمم المتحدة في التصدي لمشكلة التغير المناخي خلال الفترة 1972-2018 - راشي طارق (My University, 2020)
يهدف هذا البحث إلى محاولة حوصلة مسيرة جهود منظمة الأمم المتحدة في التصدي لمشكلة التغير المناخي عبر جملة المؤتمرات الدولية خلال الفترة 1972-2018. وقد توصل هذا البحث إلى أنه على الرغم من المسيرة الحافلة لجهود منظمة الأمم المتحدة عبر العديد من المحطات التاريخية خلال الفترة 1972-2018 بشأن التغير المناخي، تبقى محصلة النتائج دون المستوى المطلوب، الذي يحقق الأهداف المرجوة في ما يخص تخفيض الإنبعاثات الغازية المسببة للإحتباس الحراري، للحد من إرتفاع درجة الحرارة من درجة ونصف إلى درجتين مئويتين. ومن الواضح أنه دون اتفاق أوروبي أميركي وصيني على الأهداف الرقمية والجدول الزمني، فإن المفاوضات سوف تسير إلى ما لا نهاية، ويستمر مناخ الكوكب بالتغير حتى يصل إلى مرحلة لا يمكن التراجع عنها. The aim of this research is to try to get you the path of the United Nations Organization’s efforts in addressing the problem of climate change through all the international conferences during the period 1972-2018. The research found that, despite the United Nations Organization’s efforts through many historical stations during the period 1972-2018 on climate change, the results of the results remain below the required level, which achieves the desired goals in reducing greenhouse gas emissions to reduce the increase in temperature from a degree and a half to two degrees Celsius. It is clear that without a European and US agreement on the digital targets and timetable, the negotiations will go on indefinitely, and the planet's climate continues to change until it reaches an irreversible stage. The aim of this research is to try to chart the path that global attention has taken to the problem of climate change in recent decades by drawing up the overall picture of the major stations that have been successively integrated into the historical process of the international community's conferences through the United Nations Gateway to Climate Change during the period 1972-2018. The research found that, despite the international community's long journey through many historical stations during the period 1972-2018 on climate change, the results of the results remain below the required level, which achieves the desired goals in reducing greenhouse gas emissions to reduce the increase in temperature from a degree and a half to two degrees Celsius. It is clear that without a European and US agreement on the digital targets and timetable, the negotiations will go on indefinitely, and the planet's climate continues to change until it reaches an irreversible stage.